Reflexiones sobre la complejidad del quehacer antropológico, nuestra posicionalidad, y subjetividades en la frontera (EEUU-México) - De la Piedra, María Teresa (2018)
In this article, we present our experiences as researchers - activists, who have analyzed the US - Mexico border through our ethnographies. We will present reflections about our positionalities and subjectivities as activists, teachers, scholars, and residents of this border region. We conduct two different ways of activist research that we call 1) activist ethnography in the classroom, and 2) activist ethnography on the streets. We discuss the characteristics of eachone of these forms of activist research, the commonalities and differencesof both ways. We present our findings involving our own autobiographies and a theoretical analysis drawing from other activist - researchers who also use ethnography for research and activism.